1913 in Indonesian History: Demanding Equality, Changing Mentality. Issue 2 (November 2020) - Luttikhuis, Bart; van der Meer, Arnout H. C.
Abstract: In 1913, a new generation of Indonesians asserted their agency by publicly demanding equality in colonial society. Through four case studies—the prohibition of traditional forms of deference, the sudden popularity of Western dress, the adoption of new legal assimilation guidelines for Indonesians, and the discussion of employee rights at a railway company—we argue that this new assertiveness reflected a broad change in mentality that we consider a turning point in Indonesian history. By focusing on Indonesian agency, we challenge the Eurocentric periodization of the Indonesian past that emphasized WWI as a trigger of change.